ANALISIS DESKRIPTIF DATA KUESIONER: MODEL SIMULASI EVALUASI KEPUASAN MAHASISWA TERHADAP PLATFORM E-LEARNING - Olya Zapitri; Sadiah; Nonik Pratiwi Ningsih; Sudirman; Edy Waluyo (STKIP Subang, 2026)
The comprehensive transformation of higher education infrastructure toward a digital ecosystem necessitates extensive institutional monitoring to safeguard academic pedagogical standards. This study delineates the structured implementation of a quantitative descriptive statistical model tailored to analyze empirical questionnaire datasets evaluating student satisfaction with e-learning accessibility. Employing a strict quantitative descriptive method, the operational framework compiled empirical tracking data derived from a 5-point Likert scale questionnaire, which was administered to a simulation sample consisting of 10 active university students. The operationalized data analysis system strictly progressed through five interconnected, validation-oriented technical stages: editing, coding, tabulating, and deep computation of mathematical descriptors encompassing both central tendency parameters (mean, median, and mode) and precise metrics of statistical dispersion (standard deviation). The analytical results established that the general satisfaction index converged smoothly at a mean score of 4.0 (categorized systematically as